Slavery, disease, and suffering in the southern Lowcountry - McCandless, Peter (Cambridge studies on the American South., 2011)
"In 1776, the Carolina lowcountry was the wealthiest and unhealthiest region in British North America. This book argues that the two were intimately connected, examining how people created, combated, avoided, and denied the virulent disease environment; and how disease and human responses to it influenced the region, the South, and the United States"--